Standards of Nutritional Care for Patients with Cystic Fibrosis: A Methodological Primer and AGREE II Analysis of Guidelines - Maria G. Grammatikopoulou; Tonia Vassilakou; Dimitrios G. Goulis; Xenophon Theodoridis; Meletios P. Nigdelis; Arianna Petalidou; Konstantinos Gkiouras; Dimitrios Poulimeneas; Olga Alexatou; Kyriaki Tsiroukidou; Georgios Marakis; Zoe Daniil; et al. (Children, 2021)
Although many Clinical Practice Guidelines (CPGs) have been published for the care of patients with Cystic Fibrosis (CF), including a variety of nutrition recommendations, the quality of these CPGs has never been evaluated. The aim of this study was to compare, review, and critically appraise CPGs for the nutritional management of CF, throughout the lifespan. We searched PubMed, Guidelines International Network (GIN), ECRI Institute, and Guidelines Central for CPGs, with information on the nutritional management of CF. Retrieved CPGs were appraised by three independent reviewers, using the Appraisal of Guidelines, Research and Evaluation II (AGREE II) instrument and checklist. A total of 22 CPGs (seven solely nutrition oriented), by 14 different publishers, were retrieved. The Thoracic Society of Australia and New Zealand CPGs scored the highest overall quality (94.4%), while the Paediatric Gastroenterology Society/Dietitians Association of Australia CPGs had the lowest score (27.8%). Great variation in AGREE II domain-specific scores was observed in all CPGs, suggesting the existence of different strengths and weaknesses. Despite the availability of several CPGs, many appear outdated, lacking rigor, transparency, applicability, and efficiency, while incorporating bias. Considering that CPGs adherence is associated with better outcomes and the need for improving life expectancy in patients with CF, the development of CPGs of better quality is deemed necessary.